1995
DOI: 10.1001/archinte.155.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid intake and long-term risk of coronary heart disease and cancer in the seven countries study

Abstract: Average flavonoid intake may partly contribute to differences in coronary heart disease mortality across populations, but it does not seem to be an important determinant of cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
645
5
26

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 826 publications
(689 citation statements)
references
References 0 publications
13
645
5
26
Order By: Relevance
“…Most previous studies have focused on the flavonols and flavones, and many published intakes are based on the content of these two flavonoid groups only. (27,28) Our FFQ estimated that the mean intake of dietary flavonoids was 307 AE 199 mg/d in our population. This is greater than that found by Kyle, (29) who used 4-day food diaries to estimate intakes in 81 Scottish men and women (median intake 132 mg/d), although the proportional contribution by individual flavonoids to total flavonoid intake was analogous with this study.…”
Section: Discussionmentioning
confidence: 94%
“…Most previous studies have focused on the flavonols and flavones, and many published intakes are based on the content of these two flavonoid groups only. (27,28) Our FFQ estimated that the mean intake of dietary flavonoids was 307 AE 199 mg/d in our population. This is greater than that found by Kyle, (29) who used 4-day food diaries to estimate intakes in 81 Scottish men and women (median intake 132 mg/d), although the proportional contribution by individual flavonoids to total flavonoid intake was analogous with this study.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, flavonol intakes have been reported to vary widely across countries (Hertog et al, 1995) with some of the lowest intakes being reported for Northern European populations (Knekt et al, 1996), while populations from the US (Yochum et al, 1999) and other European countries have among the highest reported intakes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the intake of flavonoids in relation to coronary heart disease (CHD) Hertog et al, 1995;Knekt et al, 1996;Rimm et al, 1996;Yochum et al, 1999;Huxley and Neil, 2003;Lagiou et al, 2004;Arts and Hollman, 2005). Most of these studies have indicated a weak inverse association of flavonoids with CHD, the evidence pointing mostly to flavonols (Huxley and Neil, 2003;Arts and Hollman, 2005), flavones (Arts and Hollman, 2005) and flavan-3-ols (Lagiou et al, 2004;Arts and Hollman, 2005).…”
Section: Introductionmentioning
confidence: 99%